From vine to value: Scalable association model for resilient sweetpotato seed systems - Edson, S.; Ogero, K. (2025)
This case study documents the establishment and growth of the CHAWAVITA (Chama cha Wazalishaji na Wauzaji wa Mbegu Bora na Mazao ya Viazi Vitamu Kanda ya Ziwa) association in Tanzania’s Lake Zone, which brings together certified sweetpotato seed producers to strengthen coordination, certification, and market access. Since its registration in 2022, CHAWAVITA’s membership has grown from 28 to 53 by 2025. The association facilitates access to early generation seed (EGS), certification, and institutional markets in collaboration with TARI, TOSCI, and CIP. Over 17.6 million vine cuttings worth USD 83,306 have been sold by members since inception, including 753,000 certified cuttings in 2024 alone. The model demonstrates how collective organization enhances efficiency, quality, and sustainability of seed systems.